Perlindungan Hukum Terhadap Konsumen dari Praktik Hidden Cost dalam Perjanjian Pinjaman Online Berdasarkan Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen - Rifqi Salam Muhammad Shahih; Hesti Dwi Astuti; Leny Megawati (Program Studi Ilmu Hukum, Universitas Kuningan, 2026)
The massive growth of financial technology-based online lending services in Indonesia has given rise to a serious legal problem, namely the practice of hidden cost imposed upon consumers without prior adequate disclosure of fee information. This study aims to analyze the legal framework governing cost transparency in online loan agreements, to identify the factual forms of hidden cost practices, and to examine the legal protection available to consumers under Law Number 8 of 1999 on Consumer Protection. The normative juridical method with descriptive-analytical specification was employed, with primary legal materials comprising the Consumer Protection Law, the Civil Code, and OJK Regulation Number 10/POJK.05/2022. The findings indicate that cost transparency regulations are normatively available; however, the absence of an explicit definition of hidden cost in POJK 10/2022 creates a normative gap that enables providers to claim formal compliance without fulfilling the substantive requirements of transparency. Hidden cost practices manifest in three forms: administrative fee deductions from disbursed funds without prior notice, imposition of disproportionate service fees, and progressive late payment penalties whose calculation mechanisms are not disclosed from the outset of the agreement all of which violate Article 18 of the Consumer Protection Law and potentially undermine the free consent requirement under Article 1320 of the Civil Code. Legal protection operates through a preventive channel in the form of transparency obligations and a repressive channel comprising clause nullification and compensation liability; however, its effectiveness will only be optimal when provider substantive compliance, non-merely-formal OJK supervision, and consumer legal awareness operate simultaneously and sustainably.